The role of DC subgroups in the pathogenesis of asthma - Xu, Jiangang; Cao, Shuxian; Xu, Youhua; Chen, Han; Nian, Siji; Li, Lin; Liu, Qin; Xu, Wenfeng; Ye, Yingchun; Yuan, Qing (Frontiers in Immunology, 2024)
Dendritic cells (DCs), specialized antigen-presenting cells of the immune system, act as immunomodulators in diseases of the immune system, including asthma. The understanding of DC biology has evolved over the years to include multiple subsets of DCs with distinct functions in the initiation and maintenance of asthma. Moreover, most strategies for treating asthma with relevant therapeutic agents that target DCs have been initiated from the study of DC function. We discussed the pathogenesis of asthma (including T2-high and T2-low), the roles played by different DC subpopulations in the pathogenesis of asthma, and the therapeutic strategies centered around DCs. This study will provide a scientific theoretical basis for current asthma treatment, provide theoretical guidance and research ideas for developing and studying therapeutic drugs targeting DC, and provide more therapeutic options for the patient population with poorly controlled asthma symptoms.